KESEDIAAN MEMBAYAR WORKSHOP KELAS SENI DI KOMUNITAS PERKOTAAN BESAR DI INDONESIA - Widyaningrum, Tri; Fortunia, Evelyn Erlina; Widianto, Dimas Radityo; Nugroho, Ariq Kamil; Simatupang, Parhimpunan (JURNAL LENTERA BISNIS, 2026)
The increasing popularity of creative and experiential activities within Indonesia's urban centers has generated a marked public interest in art education. Nevertheless, there is an absence of empirical data regarding the determinants of consumers' willingness to pay for these services. This research employs a mixed-methods approach, commencing with a qualitative phase. This phase seeks to examine consumer motivations, their perception of value, and their expectations regarding the pricing of art classes. The creation of quantitative instruments for the subsequent validation phase is informed by data from interviews and open-ended survey responses. This study investigates three primary factors influencing willingness to pay (WTP): individual characteristics (including previous workshop attendance, employment status, monthly income, and age), perceptions related to the workshop (specifically, duration, instructor quality, and provider reputation), and price-value evaluations (comprising perceived value relative to cost and additional benefits). The quantitative phase assesses the robustness and significance of these connections. It emphasizes consumers' highest willingness to pay, their perceptions of the fairness of base prices, and their readiness to pay for additional benefits. This study provides a comprehensive analysis of customer behavior in the art workshop industry through the integration of qualitative insights and quantitative validation. The results give significant insights for service providers aiming to formulate pricing strategies, improve service quality, and align their value propositions with the preferences of urban consumers in Indonesia.